A better way to carry out a preseptal transconjunctival approach to the orbit. Issue 1 (January 2022) - Aslam-Pervez, Bilal; Laraway, David
Abstract : Introduction: The most common approaches taught in the United Kingdom to the orbital floor are subciliary, subtarsal, infraorbital rim and transconjunctival. Orbital floor fractures may be reached via 2 types of conjunctival approaches; the preseptal and post/retroseptal. Whilst the retroseptal approach offers a more direct and easier route to the orbital rim and floor, it is associated with a higher rate of lower lid complications compared to the preseptal approach. We will focus on the preseptal transconjunctival approach. Methods: A modified technique in Glasgow provides excellent exposure via a preseptal transconjunctival approach. The team will present a high definition recording of key steps to allow access to the orbital floor in a few minutes. Results: This approach is surgically similar in providing exposure and access, but aesthetically superior to other approaches and has minimal complications. There are limited disadvantages to transconjunctival preseptal approach, if performed meticulously with sound knowledge of anatomy of peri-orbital tissues. Conclusions: Although technically more demanding than the post/retroseptal approach, the preseptal approach enables a large and safe access to the entire orbital floor by passing through an anatomical bloodless plane. This approach can also be combined with a lateral canthotomy/cantholysis and with a medial caruncular transconjunctival incision, thus providing extended exposure of the entire orbit.